Impact of awareness campaign for enhancing adoption of new cactus pear accessions in Jordan - Hassan, Sawsan; Kaabneh, Awad; Haddad, Nizzar; Louhaichi, Mounir (International Society for Horticultural Science, 2022)
Cactus pear (Opuntia ficus-indica (L.) Mill.) fruits are increasingly in demand by consumers in Jordan and across the Mediterranean region. For many decades, the only cactus pear fruit available in local markets were the yellow-orange fruits. Recently, over 50 new cactus pear accessions with different genetic and morphological traits and different fruit colors ranging from white to red have been introduced and evaluated at Mushaqqar research station at the National Center for Agricultural Research (NARC) in Jordan. Awareness campaigns using field days, broadcasting through local media channel and farmer-to-farmer visits have been used to promote adoption and change consumer behavior. The objective of this study was to evaluate the impact of an awareness campaign aimed at boosting the adoption of new cactus pear accessions in Jordan. The data were collected from a survey of 100 households who recently received the new cactus pear accessions. The results revealed that 50 percent of farmers were aware of the new accessions through television. The new cactus pear accessions created enough interest among 25 percent of the farmers surveyed to start cactus pear cultivation for their own consumption and influenced at least 15% to start planting cactus pear as a business opportunity. Farmers who already have cactus plantations think the new accessions will bring a better market price. These findings suggest that raising awareness about new agricultural technologies can increase adoption and mainstream media could be an effective way to disseminate the new cactus pear accessions and offer an opportunity to help farmers diversify their products and increase their incomes.